Study of Water Pollution Control Law in Sikendil and Selilin Rivers, Semarang Regency - Hoya, Ade Lenty (Indonesian Journal of Environment and Sustainability Issues, 2024)
Global environmental monitoring shows that conditions in developing countries are increasingly worrisome. Water pollution is a problem that often occurs. There are 82% of 550 popular rivers in Indonesia that are damaged by pollution. Rivers are synonymous with irrigation sources, household water supplies, industrial needs, and others, so they cause serious hygienic and ecological problems. However, water's current existence is based on environmental disasters, land use, geopolitical conflicts, pollutants, and population growth. This paper aims to determine the efforts to control pollution in dealing with river pollution problems legally and provide recommendations for a River Management Strategy based on experts' opinions in the field of water resources as an alternative to pollution control. The method used is descriptive qualitative to describe efforts to control river pollution and river management strategies. This research is focused on the problems of the Sikendil River and the Selilin River in Klepu Village, Pringapus District, Semarang Regency. The results showed that controlling water pollution by stakeholders requires good coordination and facilitation from related agencies, starting from improving the social, technological, regulatory, and institutional foundation and the ecological foundation of the industry and surrounding communities so that river pollution problems can be resolved. Environmental policies in the form of law enforcement and stakeholder support are needed to improve the environment and oversee the course of environmental problems. The most dominant and most important aspect is social institutions with a value of 0.427, and the most dominant alternative is community participation with a value of 0.546, so that the aspect of social institutions with alternative community participation can be the most prioritized strategy to be applied in cases of legal river pollution.